The Effect Of Performance Evaluation On Employee Performance At The Investment Office, Dairi Regency One-Stop Integrated Service For Manpower - Debby Nur Malawati; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study was to determine and analyze the effect of Performance Evaluation on Employee Performance at the Investment Service and One-Stop Integrated Services for Manpower in Dairi Regency. This study employed a quantitative associative causal approach. The sample consisted of all civil servant employees, totaling 39 individuals, selected using purposive sampling. The results showed that Performance Evaluation had a positive and significant effect on Employee Performance. This was indicated by a t-value of 44.054, which was greater than the t-table value of 1.66412, with a significance value of 0.000, which is less than 0.05. The regression coefficient showed that for every 1-unit increase in Performance Evaluation, Employee Performance would increase by 0.957 units, assuming other variables remained constant. Additionally, the determination test results showed an Adjusted R Square value of 0.950 or 95.00%, indicating that Performance Evaluation had a very high impact on Employee Performance, while the remaining 5.00% was influenced by other factors not examined in this study. Therefore, it can be concluded that, partially, Performance Evaluation had a positive and significant effect on Employee Performance at the Investment Service and One-Stop Integrated Services for Manpower in Dairi Regency. This finding identifies that improvements in Performance Evaluation can contribute to enhancing Employee Performance.